Factors influencing methamphetamine use among Lahu hill tribe youth in Chiang Rai, Thailand: A case‒control study - Phootawan Thinpanyawong; Tawatchai Apidechkul; Karl Peltzer; Pilasinee Wongnuch (PLoS ONE, 2026)
Background Methamphetamine (MA) use presents a significant public health issue that strongly affects human health and social security. Marginalized populations, including youth from the Lahu tribe, which represents the second-largest hill tribe living in the remote border areas of northern Thailand, are among the most vulnerable to MA use. This study aimed to determine the factors associated with MA use among Lahu youths aged 15–24 years who lived in Chiang Rai Province, Thailand. Methods A case‒control study was conducted to determine the factors associated with MA use among Lahu youths aged 15–24 years. The Lahu youths who used MA were considered cases of MA use, and those who never used MA were considered controls. The participants were randomly recruited from Mae Suai, Mae Chan, Mae Fah Luang, and Muang Districts, Chiang Rai Province, Thailand, the areas of Thailand most commonly populated by the Lahu people. A validated questionnaire was used to collect data, and multiple logistic regression was used to detect association factors with a statistical significance set at α = 0.05. Results A total of 136 cases and 272 controls were included in the study. The majority of the participants were male (79.4%), 77.9% held a Thai national identification card, and 24.0% had completed primary school. After controlling for age, those females were 5.29-fold (95% CI = 2.02–13.89) more likely to use MA than males. Those with easy-to-access MA had a 2.28-fold (95% CI = 1.14–4.54) higher likelihood of MA use than those who had difficulty accessing. Those who had no schooling had a 4.29-fold (95% CI = 1.17–15.73) higher likelihood of MA use than those who had vocational and university education. Those who were unemployed had a 3.92-fold (95% CI = 1.14–13.37) higher likelihood of MA than those who were students. Those who smoked or had ever smoked had a 29.08-fold (95% CI = 11.57–73.12) greater likelihood of MA use than those who never smoked. Those who drank alcohol had a 2.53-fold (95% CI = 1.05–6.11) higher likelihood of MA use than those who did not. Those who had high knowledge scores of MA prevention and control would be more likely to use MA than those who had lower scores (AOR = 1.29; 95% CI = 1.11–1.50). Conclusions An effective intervention and policy that focuses on females with low levels of education, unemployed, and having a history of substance use should be urgently developed and implemented to reduce MA use among Lahu youths.